Hemolytic and nonhemolytic vancomycin-resistant Enterococcus faecalis isolated from beef imported to Malaysia - Fifadara, Nimita; Radu, Son; Hassan, Zaiton; Beuchat, Larry R.; Rusul, Gulam (Elsevier BV, 2003)
Twenty-two strains of vancomycin-resistant Enterococcus faecalis were isolated from 9 (6%) of 150 samples of frozen beef and beef products imported to Malaysia. The isolates were obtained from eight samples of beef and one sample of minced beef patty. No E. faecalis was isolated from frankfurters. Twelve of the 22 isolates (54.5%) were beta-hemolytic, and all isolates harbored the vanA gene. All vancomycin-resistant isolates were also resistant to streptomycin, erythromycin, kanamycin, bacitracin, ceftazimide, gentamycin, tetracycline, nalidixic acid, and teicoplanin; 95.4% were resistant to trimethoprimsulfamethoxazole; 68.8% were resistant to chloramphenicol; and 41% were resistant to ampicillin and penicillin. Small plasmids ranging in size from 1.5 to 5.8 kb were detected in 8 (36.4%) of 22 strains. The 22 isolates were classified into 20 random amplified polymorphic DNA types. Isolates were divided into two groups, each containing subclusters, that may reflect their clonal lineages. It is concluded that several clones of vancomycin-resistant E. faecalis are represented in the isolates obtained from beef imported to Malaysia.